2013
DOI: 10.4172/2157-7439.s15-002
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Microdissection of Protein Crystals Down to Submicron Dimensions

Abstract: IntroductionWhile, a lot of efforts are being invested at Synchrotron Radiation (SR) sources on high-throughput protein-to-structure pipe-lines in the context of structural genomics [1][2][3][4], methods allowing manipulating and tailoring of protein micro-crystals in a laboratory or SR-beamline environment have been less explored. Such techniques could, however, be useful for separating and sorting crystals from a batch, for dissection of crystals, polymorphs or crystalline domains from an aggregate or a cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 65 publications
(94 reference statements)
0
10
0
Order By: Relevance
“…Recently, it was confirmed that proteins can be crystallized in undersaturation conditions using LB nanotemplate [31]. Moreover, the microcrystals obtained by this methods results to be stable to the highly intense synchrotron radiation in comparison with those obtained by classical methods [32].…”
Section: Langmuir-blodgett Protein Thin Film Nanotechnologymentioning
confidence: 75%
“…Recently, it was confirmed that proteins can be crystallized in undersaturation conditions using LB nanotemplate [31]. Moreover, the microcrystals obtained by this methods results to be stable to the highly intense synchrotron radiation in comparison with those obtained by classical methods [32].…”
Section: Langmuir-blodgett Protein Thin Film Nanotechnologymentioning
confidence: 75%
“…This, taken together with the unique properties of proteins obtained with Langmuir-Blodgett (LB)-based crystallography [31][32][33][34][35][36][37][38] that can enable new strategies for drug design (work in progress), makes the goal of cancer control tremendously ambitious.…”
Section: Discussionmentioning
confidence: 99%
“…Laser-microdissection have recently (Pechkova et al, 2013; been successfully used to dissect Langmuir-Blodgett lysozyme crystals (Nicolini and Pechkova, 2006a;2007;Belmonte et al, 2012) in order to obtain pieces of crystals of very small dimensions in conjuction with X-ray nanodiffraction techniques capable to overcome the very common problem of twinned, defect, aggregated and mosaic crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Several demonstration experiments show that lasermicrodissection techniques can also be applied to protein crystals (Pechkova et al, 2013;. We have used the term laser-microdissection for the cutting of a crystal by a laser beam into smaller pieces (Pechkova et al, 2013) while microfragmentation is used for the separation of a microdissected crystal into smaller fragments due to effects such as cavitations at domain boundaries and solvent interpenetration.We will explore in this contribution the question whether protein crystals differing in perfection and X-ray radiation stability also differ in microdissection and microfragmentation behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation